Pageoph Topical Volumes
DOI: 10.1007/978-3-7643-8124-0_2
|View full text |Cite
|
Sign up to set email alerts
|

Short-Timescale Chemo-Mechanical Effects and their Influence on the Transport Properties of Fractured Rock

Abstract: Abstract-Anomalous changes in permeability are reported in fractures circulated by fluids undersaturated with respect to the mineral host. Under net dissolution and net removal of mineral mass, fractures may alternately gape or seal, depending on the prevailing mechanical and chemical conditions. The influence on transport properties is observed to be large, rapid, and irreversible: Permeabilities may change by two orders of magnitude in a month, and the direction of permeability change may switch spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Direct observation of pressure solution was evaluated by favorable comparison of change in fracture aperture with anticipated mass removal rate measured in the experiment. This behavior is also consistent with observations of the sectioned fracture, post-test, where SEM micrographs show dissolution sites and the blunting and welding of asperity contacts in a natural fracture that had been separated prior to the test [22]. Careful characterization of the fracture topography and observations of equilibrium changes in the hydraulic apertures were available for the experiments [12] and were fit to the model of Eq.…”
Section: Arkansas Novaculitesupporting
confidence: 82%
“…Direct observation of pressure solution was evaluated by favorable comparison of change in fracture aperture with anticipated mass removal rate measured in the experiment. This behavior is also consistent with observations of the sectioned fracture, post-test, where SEM micrographs show dissolution sites and the blunting and welding of asperity contacts in a natural fracture that had been separated prior to the test [22]. Careful characterization of the fracture topography and observations of equilibrium changes in the hydraulic apertures were available for the experiments [12] and were fit to the model of Eq.…”
Section: Arkansas Novaculitesupporting
confidence: 82%
“…Although, the extrapolation to natural conditions yields enormous timescales (tens to hundreds of years) in order to observe time‐dependent deformation of minerals (Karato, ). However, some experiments on low‐porosity rock (Elsworth & Yasuhara, ) have shown that reactions involving reactive fluids (as in CO 2 storage) are fast (hours to weeks), and under relatively modest loads (~10 6 –10 7 Pa) can lead to pressure solution and effectively viscous deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the most likely mechanisms is pressure solution as observed elsewhere Elsworth and Yasuhara, 2006;Yasuhara et al, 2006b].…”
Section: Interpretation By Lumped Parameter Modelmentioning
confidence: 97%
“…Additionally, in our experiments, no particulate matter is observed in the effluent fluid, which suggests that a concept of particle‐detachment might be inappropriate as an explanation for aperture reduction. Therefore, one of the most likely mechanisms is pressure solution as observed elsewhere [ Polak et al ., ; Elsworth and Yasuhara , ; Yasuhara et al ., ].…”
Section: Interpretation By Lumped Parameter Modelmentioning
confidence: 99%
See 1 more Smart Citation